Overexpression of phosphorylated MARCKS in the nicotine-derived nitrosamine ketone induced lung cancer mice - Chen, Zhen; Gu, Ling-Yun; Zhou, Jun; Wang, Qin; Gao, Hui; Yu, Zhong-He (Bangladesh Journal of Pharmacology, 2015)
Lung cancer is the most frequently occurring lethal cancers in men and women population. The aim of the present study is to observe the overexpression pattern of phosphorylated MARCKS in the nicotine-derived nitrosamine ketone (NNK) induced lung cancer mice. Pathogen-free female A/J mice were used for the present experiment to induce lung cancer by the carcinogen namely, NNK. At different time intervals namely, 5th, 6th and 7th month after NNK injection, lung tissue samples were collected. Immunohistochemistry in accordance with the immunoblotting techniques were used to confirm the overexpression of phosphorylated MARCKS in the NNK induced lung cancer mice model. The present study concludes that the phosphorylated MARCKS was overexpressed in the NNK induced lung cancer mice during the early stages of lung cancer and it may be used as a tool to detect the lung cancer in the initial stages.